Transformasi Pembelajaran Digital terhadap Kualitas Interaksi Guru dan Siswa di Era Artificial Intelligence - Muhammad Syifa’ Mashudi; Imron Fauzi; M Ilmil Zawawi (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
This study aims to analyze the transformation of digital learning on the quality of interaction between teachers and students in the era of artificial intelligence (AI). The development of digital technologies and the integration of AI in education have reshaped communication patterns, increased student engagement, and simultaneously created new challenges in maintaining emotional closeness between teachers and learners. This research employed a qualitative approach with data collected through interviews, observations, and documentation over a three-month period in several elementary and secondary schools. The findings indicate a shift in teacher–student communication from one-way delivery toward more collaborative, digitally mediated interactions. Student engagement also increased significantly through the use of interactive learning platforms, gamification, and AI-based adaptive systems. However, teachers reported difficulties in sustaining emotional connection due to limited nonverbal communication in virtual environments. These findings suggest that the effectiveness of digital learning transformation is not solely determined by technological capability, but also by teachers’ socio-emotional competencies in fostering meaningful pedagogical relationships. The study recommends the need for digital literacy training and virtual empathy development for educators to ensure that AI integration enhances interaction quality without diminishing the humanistic dimension of education.